Character Strengths of Indonesian Secondary Students in the Digital Age - Abie Syifa Mahendra; M Muslikah (Universitas Negeri Padang, 2026)
The digital era raises questions about how students' character strengths operate in technology-saturated environments. This study aimed to map character strengths profiles across three Indonesian secondary school types—Islamic (MA), general (SMA), and vocational (SMK)—and to compare these profiles by gender. A sequential explanatory mixed-methods design was used. Quantitative data were collected from 360 students using an adapted VIA Inventory of Strengths questionnaire; qualitative data were gathered through in-depth interviews with nine purposively selected students. Quantitative analyses included descriptive statistics, independent t-tests, effect sizes (Cohen's d) interpreted using Gignac & Szodorai's (2016) guidelines, and thematic analysis. Three main findings emerged. First, Hope and Gratitude were consistently high across all three school types, while Creativity, Perspective, and Leadership were consistently low. Second, gender differences varied by school type: significant differences were found in MA and SMK. Third, qualitative interviews revealed that students with low self-reported creativity still described creative ideas when asked directly. In practice, these findings suggest that school counselors might supplement questionnaires with open-ended questions. Limitations include non-probability sampling, cross-sectional design, and single-item measures.